The Influence of pH on Phase and Morphology of BiOIO3 Nanoplates Synthesized by Microwave-Assisted Method and Their Photocatalytic Activities - Panudda Patiphatpanya (2019)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. The influence of precursor solution pH on phase, morphology and optical properties of BiOIO3 was investigated in this research. The products were synthesized in the solutions with the pH of 2, 3, 4, 5 and 6 by a 360 W microwave (2.45 GHz) at 5 min/cycle for 12 cycles (60 min) and were well characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, selected area electron diffraction, UV–visible spectroscopy, photoluminescence spectroscopy and Brunauer–Emmett–Teller surface area analysis. According to the analytical results, pure BiOIO3 nanoplates were synthesized at the pH of 2 and 3 and were transformed into pure Bi2O3 nanoparticles at the pH of 6. The photocatalytic activities of products were studied through the degradation of rhodamine B solutions under visible light irradiation. The as-synthesized BiOIO3 nanoplates with band gap energy of 2.90 eV synthesized at the pH of 3 have the highest decolorization efficiency of 97.9% and pseudo-first-order degradation rate of 0.0442 min−1 within 60 min.